Memahami Strategi QISCUS untuk Unggul dalam Ketidakpastian Lingkungan Bisnis yang Tinggi - Luqman Tifa Perwira; Sito Meiyanto (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
Technology based company operates in a very dynamic business environment. As one of the fast growing technology company, Qiscus has proven themselves to be able to survived after several major change in their business. This study aimed to find out what strategies taken by Qiscus, as a startup company and how their strategy can be used to deal with this high uncertainty business environment. A qualitative method with case study approach was used to answer these research questions. Data were gathered from 8 informants (2 founders and 6 senior employees). Through the in-depth interview and observation processes, the study found six strategic themes which were then categorized into internal and external strategies. The research findings showed that Qiscus had implemented six strategies: high involvement organization, pivot, building brand image, maintaining users experience, strategic investment and market education. The findings support previous studies that stated organizations with strong internal stakeholder involvement tend to have better performance and productivity.